Bad Loans During the Period 2019 – 2021 in Bulgaria – Dynamics and Trends - Stoyanova, Nora (Research Papers, 2025)
The focus of this report is the dynamics of "bad loans" in Bulgaria over the period 2019 – 2021 and the impact of the economic consequences of Covid-19 on the banking sector. The continuous development and expansion of lending activities, the creation of various credit products, the competitiveness of the credit market, and the drive to attract more clients contribute to the emergence of non-performing loans. The analysis examines the reasons for the increase in non-performing loans, noting that despite a temporary rise during the pandemic, their levels have stabilized to those of the pre-crisis period. Attention is also given to regional disparities and economic factors, such as unemployment and lack of investment, which lead to difficulties in servicing loans in certain regions.